Karakterisasi Biopolimer Kitosan Hasil Deasetilasi Limbah Kepiting Rajungan (Portunus Sanginolentus) Menggunakan NaBH4 Dalam NaOH - Hasanela, Nurani; Tanasale, Matheis F.J.D.P.; Tehubijuluw, Helna (Indonesian Journal of Chemical Research, 2020)
The chitosan isolation from crab crab waste (Portunus sanginolentus) has been carried out. Chitin production is carried out by the de-proteination, demineralization and depigmentation processes. Chitosan biopolymer is produced from chitin through de-acetylation method using base solution (NaOH) and the addition of NaBH4 which aims to increase the degree of de-acetylation (DD) of chitosan. The results of 25 g of chitin obtained chitosan amounted to 16.67 g (66.68%). Chitin and Chitosan were identified by a Fourier Transform Infrared (FT-IR) spectrophotometer.